Correlation between sleep parameters and VO2max in physiotherapy students (KHD-Production, 2025)
Sleep quality and quantity are essential for health and academic success in university students. This study examined the relationship between physical fitness and sleep parameters in physiotherapy students. Seventy-one healthy female physiotherapy students aged 18-24 from Walailak University participated in this cross-sectional study. Participants had normal BMI and mood conditions. The Pittsburgh Sleep Quality Index (PSQI) assessed sleep quality and quantity. Physical fitness was measured using the Astrand-Rhyming test protocol to determine maximum oxygen consumption (VO2max). Spearman's rank-order correlation analysis was performed to examine associations between variables. The global PSQI score was significantly negatively correlated with age (r = −0.297, p = 0.01). However, VO2max showed no significant correlation with sleep quality (r = 0.133, p = 0.27) or sleep quantity (r = -0.026, p = 0.82). No significant associations were found between VO2max and the overall PSQI score or individual PSQI components. As measured by VO2max, physical fitness does not significantly influence sleep quality or quantity in healthy female physiotherapy students. These findings suggest that factors other than physical fitness may be more important determinants of sleep in this population.